Penerepan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) pada Materi Kekongruenan Bangun Datar - Halimatussa’diah; Raoda Ismail; Pitriana Tandililing; Dewi Kristika Findia Ning Tyas; Elsi Sirampun (EDUPEDIA PUBLISHER, 2026)
Purpose: This study aimed to describe the implementation of the Student Teams Achievement Division (STAD) cooperative learning model, students’ responses and engagement during the learning process, and students’ conceptual understanding of plane figure congruence. Methodology: This study employed a descriptive method with a qualitative approach and was conducted in Grade 7 of Muhammadiyah Junior High School Jayapura during the 2025/2026 academic year, involving 30 students as research participants. Data were collected through observations, interviews, tests, and documentation. Data validity was ensured through source triangulation and technique triangulation, while data analysis was carried out using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. Findings: The findings revealed that the STAD cooperative learning model was implemented in accordance with the planned instructional stages: class presentation, team study, quizzes, individual improvement scores, and team recognition. During the learning process, students demonstrated positive responses through active participation in group discussions, confidence in expressing their opinions, and collaboration in completing assigned tasks. Significance: Interactions among students within heterogeneous groups provided opportunities for peer support in understanding the concept of plane figure congruence. Students’ conceptual understanding was reflected in their ability to identify corresponding elements of congruent figures, explain concepts in their own words, and solve problems related to the material being studied. Overall, the findings indicate that STAD supports active student engagement and the development of conceptual understanding of plane figure congruence.